2021
DOI: 10.1242/jcs.256180
|View full text |Cite
|
Sign up to set email alerts
|

Endogenously expressed Ranbp2 is not at the axon initial segment

Abstract: Ranbp2 (also known as Nup358) is a member of the nucleoporin family that comprises the nuclear pore complex. Ranbp2 localizes at the nuclear membrane and was recently reported at the axon initial segment (AIS). However, we show the anti-Ranbp2 antibody used in previous studies is not specific for Ranbp2. We mapped the antibody binding site to the amino acid sequence KPLQG that is present in both Ranbp2 and Neurofascin, a well-known AIS protein. After silencing Neurofascin expression in neurons, the AIS was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The sgRNAs and the homology-independent donor templates were generated following strategies similar to those described previously 19, 22, 23, 58 . Briefly, the U6 promoter and scaffold sequences were PCR amplified from pMJ117 and pMJ179 (gifts from Jonathan Weissman, Addgene plasmid #85997 and #85996).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sgRNAs and the homology-independent donor templates were generated following strategies similar to those described previously 19, 22, 23, 58 . Briefly, the U6 promoter and scaffold sequences were PCR amplified from pMJ117 and pMJ179 (gifts from Jonathan Weissman, Addgene plasmid #85997 and #85996).…”
Section: Methodsmentioning
confidence: 99%
“…However, antibodies are frequently non-specific and for reasons that are unclear, many antibodies that label AIS are not against their claimed targets 1820 . Therefore, to circumvent some of the challenges associated with antibodies and to look for AIS- and axon-enriched proteins, we performed CRISPR-mediated epitope tagging of endogenous proteins 19, 2123 . We selected 23 different candidates (Fig.…”
Section: Mainmentioning
confidence: 99%
“…V5 tag knock-in sgRNA and donor constructs were generated following strategies similar to those described previously 6, 7 . Adeno-associated virus (AAV) cell-lysates were produced using the AAVpro Purification Kit (All Serotypes) (Takara) with slight modifications.…”
Section: Methods Detailsmentioning
confidence: 99%
“…V5 tag knock-in sgRNA and donor constructs were generated following previously described strategies 44, 56 . The specific target sequences of guide RNA (gRNA) were designed for knock-in: rat Scrib 5’-GGGAAGCACCTGGCCCTAGG-3’; rat Wdr47 5’-TCTGGACTTACAGTGGCTAG-3’; rat Wdr7 5’-ACGGCAGTCAGACCATGAAG-3’; mouse Scrib 5’-GTCCCGGCCGCACAGACCGA-3’.…”
Section: Methodsmentioning
confidence: 99%
“…It also contains an N-terminal leucine rich region or leucine domain, a zinc finger domain containing eight zinc finger motifs, four Ran binding domains, a kinesin binding domain, an E3 SUMO ligase domain, and a cyclophilin homologous domain ( Figure 2 ). While several reports indicated localization at the axon initial segment (AIS) of neurons ( 39 , 40 ), the use of more specific antibodies has recently demonstrated that endogenous RanBP2 is not found in the AIS ( 41 ).…”
Section: Ranbp2mentioning
confidence: 99%